Distribution and biomarker of carbon‐14 labeled fullerene C60 ([14C(U)]C60) in pregnant and lactating rats and their offspring after maternal intravenous exposure. Issue 12 (17th June 2015) - Snyder, Rodney W.; Fennell, Timothy R.; Wingard, Christopher J.; Mortensen, Ninell P.; Holland, Nathan A.; Shannahan, Jonathan H.; Pathmasiri, Wimal; Lewin, Anita H.; Sumner, Susan C. J.
Abstract A comprehensive distribution study was conducted in pregnant and lactating rats exposed to a suspension of uniformly carbon‐14 labeled C60 ([14C(U)]C60). Rats were administered [14C(U)]C60 (~0.2 mg [14C(U)]C60 kg–1 body weight) or 5% polyvinylpyrrolidone (PVP)‐saline vehicle via a single tail vein injection. Pregnant rats were injected on gestation day (GD) 11 (terminated with fetuses after either 24 h or 8 days), GD15 (terminated after 24 h or 4 days), or GD18 (terminated after 24 h). Lactating rats were injected on postnatal day 8 and terminated after 24 h, 3 or 11 days. The distribution of radioactivity in pregnant dams was influenced by both the state of pregnancy and time of termination after exposure. The percentage of recovered radioactivity in pregnant and lactating rats was highest in the liver and lungs. Radioactivity was quantitated in over 20 tissues. Radioactivity was found in the placenta and in fetuses of pregnant dams, and in the milk of lactating rats and in pups. Elimination of radioactivity was < 2% in urine and feces at each time point. Radioactivity remained in blood circulation up to 11 days after [14C(U)]C60 exposure. Biomarkers of inflammation, cardiovascular injury and oxidative stress were measured to study the biological impacts of [14C(U)]C60 exposure. Oxidative stress was elevated in female pups of exposed dams. Metabolomics analysis of urine showed that [14C(U)]C60 exposure to pregnant rats impacted the pathways of vitamin B, regulation of lipid and sugar metabolism and aminoacyl‐tRNA biosynthesis. This study demonstrated that [14C(U)]C60 crosses the placenta at all stages of pregnancy examined, and is transferred to pups via milk. Copyright © 2015 John Wiley & Sons, Ltd.